2019
DOI: 10.1007/s00029-019-0470-2
|View full text |Cite
|
Sign up to set email alerts
|

R-systems

Abstract: Birational toggling on Gelfand-Tsetlin patterns appeared first in the study of geometric crystals and geometric Robinson-Schensted-Knuth correspondence. Based on these birational toggle relations, Einstein and Propp introduced a discrete dynamical system called birational rowmotion associated with a partially ordered set. We generalize birational rowmotion to the class of arbitrary strongly connected directed graphs, calling the resulting discrete dynamical system the R-system. We study its integrability from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…For the rectangle, birational rowmotion enjoys remarkable integrability properties related to cluster algebra Y-system dynamics (a.k.a., Zamolodchikov periodicity) [92]. Birational rowmotion was also the principal example motivating the recent definition of R-systems due to Galashin and Pylyavskyy [26].…”
Section: · · ·mentioning
confidence: 99%
“…For the rectangle, birational rowmotion enjoys remarkable integrability properties related to cluster algebra Y-system dynamics (a.k.a., Zamolodchikov periodicity) [92]. Birational rowmotion was also the principal example motivating the recent definition of R-systems due to Galashin and Pylyavskyy [26].…”
Section: · · ·mentioning
confidence: 99%
“…Birational rowmotion was studied by Grinberg and Roby ; Glick later showed that one of the Grinberg–Roby results was equivalent to an instance of Zamolodchikov periodicity. Most recently, Galashin and Pylyavskyy generalized the notion of birational rowmotion to strongly connected directed graphs by introducing R‐systems .…”
Section: History and Examplesmentioning
confidence: 99%
“…Rowmotion is an action originally defined on hypergraphs by P. Duchet [13] and generalized to order ideals of an arbitrary finite poset by A. Brouwer and A. Schrijver [7]. Given I ∈ J(P ), rowmotion on I, denoted Row(I), is the order ideal generated by the minimal elements of P \ I. Rowmotion has recently generated significant interest as a prototypical action in the emerging subfield of dynamical algebraic combinatorics; see [38] for a detailed history and [3,6,10,11,12,14,15,17,18,19,21,22,26,27,28,29,35,37,36,41] for more recent developments.…”
Section: 22mentioning
confidence: 99%